KECEMASAN MASYARAKAT SAAT PENDEMI COVID-19 - Yusuf Hasan Baharudin (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
Overcoming the Covid-19 pandemic by breaking the chain of transmission is a very important thing to do considering the dangerous impacts of the disease outbreak, not only health impacts, but also educational impacts, economic impacts, social impacts, and all its derivatives. Of course, it is very concerning, how people are anxious to carry out projects because they are afraid of being infected, places of worship become deserted from worship activities, economic activities are sluggish, places for children's learning become less useful. All of this must not continue and must be immediately addressed not only by the Indonesian government but also by all levels of Indonesian society. Everyone joins hands to participate in breaking the chain of transmission of Covid-19 so that everything can return to normal. Therefore, the researcher researched mapping the types of anxiety experienced by the community, especially in the Cilacap district in the hope of becoming one of the references for the Cilacap district government's policy in dealing with the Covid-19 outbreak. This study examines the anxiety experienced by Cilacap residents during the pandemic using qualitative descriptive research.